Hands-On System Programming with Go : Build Modern and Concurrent Applications for Unix and Linux Systems Using Golang. - Guerrieri, Alex (Packt Publishing, Limited, 2019)
Go is the new systems programming language for Linux and Unix systems. After a brief introduction of Unix-based OS and of system programming, we'll dive into Go standard packages, focusing on how easily they allow to interact will all the functionality of the OS. By the end of this book, you will be comfortable with systems programming using Go.